2019
DOI: 10.1039/c9tc00488b
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated growth by flash heating of high critical current trifluoroacetate solution derived epitaxial superconducting YBa2Cu3O7 films

Abstract: Flash heating reduces the precursor nanoparticle coarsening and shortens the growth time of epitaxial YBa2Cu3O7 thin films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 58 publications
(106 reference statements)
0
25
0
Order By: Relevance
“…Further analysis of angular Jc dependences in conjunction with an advanced TEM microstructural analysis should be performed in order to elucidate the nature of pinning centers. However, considering the results obtained in other CSD films and nanocomposites studied, an enhancement of µ0H* and isotropic strong pinning contribution can be correlated with the presence of stacking faults and associated nanostrain [29,30,45,46]. Figure 7b shows the µ 0 H* values obtained for the different films as a function of T g .…”
Section: Superconducting Performancementioning
confidence: 67%
See 2 more Smart Citations
“…Further analysis of angular Jc dependences in conjunction with an advanced TEM microstructural analysis should be performed in order to elucidate the nature of pinning centers. However, considering the results obtained in other CSD films and nanocomposites studied, an enhancement of µ0H* and isotropic strong pinning contribution can be correlated with the presence of stacking faults and associated nanostrain [29,30,45,46]. Figure 7b shows the µ 0 H* values obtained for the different films as a function of T g .…”
Section: Superconducting Performancementioning
confidence: 67%
“…In the case of FH films, although a slight enhancement of µ0H* is observed at low Tg, a clear tendency cannot be identified. For those samples, the value of µ0H* is already very high at Tg = 810 °C, thus pointing out that the higher nucleation rate of FH process also helps to induce pinning defects within the matrix, which are not present with CTA growth [30]. The effect of rapid annealing on the defect structure and final properties of different functional materials has also been reported [40,41].…”
Section: Superconducting Performancementioning
confidence: 70%
See 1 more Smart Citation
“…The obtained histograms evidence that the concentration of short Y124 intergrowths (length <50 nm) is enhanced with respect to pristine films, where only a smaller number of long intergrowths (length >150 nm), principally located at the surface are formed 14 ; NCs grown using an extremely fast, flux-heating process present an even higher population of shorter (<20 nm) SF's. 20 The SF's induced in the NC by the presence of nanoparticles appear extremely rippled (Figure 2e). We analyzed as well a second YBCO+10% BYTO NC, with a similar intergrowth population, but des-oxygenated after growth, noted NC(des-ox), so as to analyze the effects on defect-driven embedded magnetism.…”
Section: Resultsmentioning
confidence: 98%
“…10,24 Particularly, in CSD nanocomposites it has been shown that vortex pinning is strongly enhanced by the concentration of these Y248 intergrowths. 9,10,25 The structure of the planar Y248 intergrowth defects has been recently analyzed in detail by Scanning Transmission Electron Microscopy (STEM). The expected composition of the Y248 intergrowth is Y 2 Ba 4 Cu 8 O 16 because they consist on an extra Cu-O chain layer inserted between two Ba-O layers, leading to a lattice expansion in c-axis direction (from 11.7 to 13.3Å).…”
Section: Introductionmentioning
confidence: 99%